2016
DOI: 10.1039/c6lc00718j
|View full text |Cite
|
Sign up to set email alerts
|

Microengineered cancer-on-a-chip platforms to study the metastatic microenvironment

Abstract: More than 90% of cancer-related deaths can be attributed to the occurrence of metastatic diseases. Recent studies have highlighted the importance of the multicellular, biochemical and biophysical stimuli from the tumor microenvironment during carcinogenesis, treatment failure, and metastasis. Therefore, there is a need for experimental platforms that are able to recapitulate the complex pathophysiological features of the metastatic microenvironment. Recent advancements in biomaterials, microfluidics, and tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 128 publications
0
79
0
Order By: Relevance
“…There have been numerous studies on tumor angiogenesis in previous years. For example, studies have revealed that the major cytokines responsible for tumor angiogenesis are secreted via the intricate interaction between tumor cells and stromal cells (5,6). Among these factors, vascular endothelial growth factor (VEGF) is pivotal as the primary molecular driver in vasculogenesis (7).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies on tumor angiogenesis in previous years. For example, studies have revealed that the major cytokines responsible for tumor angiogenesis are secreted via the intricate interaction between tumor cells and stromal cells (5,6). Among these factors, vascular endothelial growth factor (VEGF) is pivotal as the primary molecular driver in vasculogenesis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of first-generation tumour-on-achip systems include a chip in which lung cancer spheroids were embedded in micro-patterned three-dimensional matrices immediately contiguous to a microchannel lined with endothelial cells (figure 1c) [4], and a breast tumour-on-a-chip model comprised the upper and lower cell culture chambers separated by an ECM-derived membrane that mimics a basement membrane in vivo (figure 1d) [13]. Previous reviews in the literature on tumour-on-a-chip technology include the construction of three-dimensional tumour models [14][15][16][17], its applications to specific cancer studies such as metastasis [18,19], and its utilities in drug discovery [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment plays an important role in cancer initiation, progression, metastasis, and drug resistance [97]. The tumor microenvironment is the actual physiological environment supporting and regulates the development of tumor cells.…”
Section: Overview Of Cancer Metastasismentioning
confidence: 99%
“…MET also plays an important role as it enables CTCs with EMT to reverse and restore the epithelial phenotype, regain the adhesion ability to form the secondary tumor [15]. In this process, tumor cells will lose cell polarity, rearrange cell–cell junction, undergo elongation, and thereby be able to migrate to distant tissues [97]. Microfluidic systems used for monitoring EMT process have been studied in many papers [107].…”
Section: Biomimicking Of Cancer Metastasis Using Microfluidicsmentioning
confidence: 99%